Reconciling Conflicts of Human Rights Violations in Indonesia - Rachmad, Teguh Hidayatul; Setyawan, Erwin; Sasongko, Yohanes Probo Dwi (RechtIdee, 2023)
The Indonesian nation has a dark history of humanity. The existence of humanitarian violations in the G30S/PKI incident and the humanitarian tragedy in the 1998 Trisakti incident are clear evidence of gross violations of Human Rights (HAM). These violations against humanity, to this day, have not found a clear spot. So, in this regard, reconciliation is needed by presenting the theory of collective memory from Maurice Halbwachs, how in this theory we can accept the past and learn to be present and react to it properly. The mistakes that occurred in the past are history, where our nation continues to learn to become a nation that can more maturely and openly appreciate existing human values, for the sake of life and development with humanity.